Influence of learning and growth toward internal business processes: case studies on Departement of Hospital Pharmacy in DIY - Satibi; Achmad Fudholi; Hari Kusnanto; Jogiyanto (Universitas Gadjah Mada, 2011)
Hospital Pharmacy have revenue contribution to the Hospital reached 40-60%, thus becoming one of the hospital revenue center. However hospital pharmacy services in Indonesia are still many shortcomings, is considering several constraints such as the ability of pharmaceutical workers, the limited ability of hospital management, hospital management policies, and limited knowledge of the relevant parties of hospital pharmacy services. Such conditions must be efforts to change with the development of learning and growth factors, because these factors (human capital, organizational capital and information capital) and that effective management is a source of sustainable competitive advantage. The research objective is to determine the relationship and influence of learning and growth to the internal business processes in Hospital Pharmacy. Kind of research is non-experimental research is associative. Research tool includes a questionnaire indicators of learning andgrowth, and internal business processes. The subjects was the head of hospital pharmacy in the hospital region of Daerah Istimewa Yogyakarta (DIY). Sample size was 35 hospital. In addition to sending questionnaires, random interviews will be conducted on several hospital pharmacies to enrich the results of the survey questionnaire. The data was analyzed by correlation and linear regression to determine the relationship and influence the learning and growth factors to the internal business processes in hospital pharmacy. Results obtained from statistical calculations with 95% confidence show that there is a strong relationship between the organizational culture against internal business processes with r value of 0.981 with a contribution of 96.20% of theorganizational capital of the sustainability of the internal business processes in Hospital pharmacy in Yogyakarta Special Region. There is not significant relationship between the human capital against internal business processes. There is not significant relationship between the information capital against internal business processes